2020
DOI: 10.20944/preprints202004.0536.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hedging Feasibility Perspectives against the COVID-19 for the International Tourism Sector

Abstract: Nowadays tourism is growing as a gigantic, global business accounting for 10.4 % of Global GDP and 10% of global employment (Joppe, 2020). This review paper aims to explore the risks borne for tourism sector by the outbreak of corona-virus in 2020. Tourism sector is a highly vulnerable sector and the costs that will be borne from corona-virus pandemic will be devastating, particularly for the countries relying on this sector as a basic source of income. The paper suggests possible solutions and adaptation rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 10 publications
0
22
0
10
Order By: Relevance
“…Two papers compared the COVID-19 pandemic with previous public health crises. In the first study, lessons learned from previous crises and pandemics are discussed, including malaria, yellow fever, Ebola, Zika virus, Middle East respiratory syndrome (MERS-CoV), avian influenza (H5N1), Creutzfeldt-Jakob disease (Mad Cow disease), swine flu (H1N1), and severe acute respiratory syndrome (SARS) [ 22 ]. This paper concluded that the impacts of COVID-19 on the global economy and China’s tourism and hospitality industry, in particular, are likely to differ from previous pandemics, from which the tourism and hospitality industry recovered relatively quickly [ 22 ].…”
Section: Research Approaches Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Two papers compared the COVID-19 pandemic with previous public health crises. In the first study, lessons learned from previous crises and pandemics are discussed, including malaria, yellow fever, Ebola, Zika virus, Middle East respiratory syndrome (MERS-CoV), avian influenza (H5N1), Creutzfeldt-Jakob disease (Mad Cow disease), swine flu (H1N1), and severe acute respiratory syndrome (SARS) [ 22 ]. This paper concluded that the impacts of COVID-19 on the global economy and China’s tourism and hospitality industry, in particular, are likely to differ from previous pandemics, from which the tourism and hospitality industry recovered relatively quickly [ 22 ].…”
Section: Research Approaches Usedmentioning
confidence: 99%
“…However, suggestions have already been made for post-COVID-19 management of the tourism and hospitality industry. These include: (1) focusing primarily on domestic tourism; (2) ending mass tourism and pilgrimage tourism; (3) focusing more on conference tourism, virtual reality tourism, and medical tourism; and (4) building a more sustainable tourism and hospitality industry rather than a return to "business as usual" [ 21 , 22 ].…”
Section: Research Approaches Usedmentioning
confidence: 99%
“…Mensah (2020) stressed that the tourism industry has always been hardest hit by pandemics like Plagues, notably, the Black Death (1346-1353), Spanish Flu (1918)(1919)(1920), SARS (2002SARS ( -2004, H1N1 Swine Flu (2009-2010 and Ebola Virus (2014)(2015)(2016). Th e pandemic outbreaks in the last two decades are Malaria; Dengue Fever/ Yellow Fever; Ebola; Zika Virus; Middle East Respiratory Syndrome (MERS); Bird Flu or Avian Infl uenza or H5N1; Mad Cow Disease or Creutzfeldt-Jakob Disease; H1N1 or Swine Flu; SARS; and COVID-19 where the mortality rate of COVID-19 (1%-3.4%) is found lower than those of the MERS and SARS which reached 34% and 10% respectively and the seasonal fl u mortality rate is (<0.1%) (Menegaki, 2020) Th e distinction between the words pandemic; epidemic; and endemic is regularly blurred, even by medical experts (Intermountain Health Care, 2020). For instance, the sudden emergence and rapid global spread of a novel H1N1 infl uenza virus in early 2009 has caused confusion about the meaning of "pandemic" and how to recognize pandemics when they occur (Morens et al, 2009).…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
“…Zenker and Kock (2020) argue that the impact of COVID-19 pandemic on tourism industry is tremendous even in its early stage. Th e ripple eff ect of this pandemic has reverberated through every corner of the globe, causing lives and jobs of many (Mensah, 2020;Menegaki, 2020) there are 75 million jobs in tourism at immediate risk and the industry are to lose more than 2.1 trillion US$ (WTTC, 2020;in Zenker & Kock, 2020). Hung, Mark, Yeung, Chan, and Graham (2018) assumes that based on previous experiences, some hospitality-related stakeholders may be better prepared, in terms of emergency preparation and working with customers.…”
Section: Impact Of Covid-19 On Tourism Industrymentioning
confidence: 99%
See 1 more Smart Citation